Health and Lifestyles in Young Adults with Type 1 Diabetes - Serrabulho, Lurdes (2013)
The social, occupational, familiar and emotional changes during emerging adulthood, can affect adherence to diabetes management tasks and quality of life of young adults with type 1 diabetes. Aims The objectives consisted on the evaluation of behaviours and lifestyles, psychological adaptation and social support of young adults with type 1 diabetes. Methods This research included a quantitative study with 278 young adults with type 1 diabetes, between 18 and 35. Results Satisfaction with life is 6.6 ±1.7 and the several important factors in life vary from 7.2 ±1.8 (diabetes management capacity) to 9.1 ±1.4 (family), in a scale 0-10. Young adults have healthy eating habits, but only one third practice recommended physical activity. Adherence to insulin therapy and glucose monitoring is satisfactory but they present 8.7% ±1.6 as medium value for HbA1c, superior to the recommended by international guidelines. 25% present diabetes complications. Young adults consider having a good social support and refer the benefits of group sessions and summer camps with other youngsters with type 1 diabetes. Conclusions: The young adults studied showed satisfactory lifestyles, good social support and satisfaction with life, a reasonable adherence to the diabetes treatment, however with a less optimal metabolic control of diabetes.